A self-healing nav1.7 inhibiting peptide gel and preparation method and application thereof
Patent Information
- Application Number
- CN202611495909.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
这一设计颠覆了多肽在凝胶中的传统负载模式,实现了SaTx的零突释与响应性降解缓释,更集长效镇痛、高效抗炎、促进软骨修复等多重功能于一体,在KOA治疗中实现了“镇痛-抗炎-软骨修复”的协同增效作用,解决了游离多肽作用条件苛刻、疗效不显著的难题
(1)本发明首次将SaTx确立为凝胶网络形成的交联核心与必要条件,制备了SaTx结构依赖性的双组分水凝胶(PGA-Cat/CS-SH/SaTx体系)。对照实验清晰表明,单独的PGA-Cat与CS-SH混合物仅为可流动的粘稠液体,只有加入SaTx后才迅速触发凝胶化。实现了SaTx从负载药物到载体成分的根本性角色转变。
Smart Images

Figure CN122998055A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical technology, specifically to a self-healing Nav1.7 inhibitory peptide gel, its preparation method, and its application. Background Technology
[0002] Knee osteoarthritis (KOA) is the most common chronic degenerative joint disease worldwide, characterized by progressive degeneration of articular cartilage, chronic inflammation of the synovium, subchondral bone sclerosis, and osteophyte formation. Currently, clinical treatments for KOA are significantly limited. While first-line drugs such as nonsteroidal anti-inflammatory drugs (NSAIDs) can relieve short-term pain, long-term use results in significant side effects. For advanced-stage patients, joint replacement surgery can restore function, but it carries risks such as high cost, significant trauma, and prosthesis loosening. Therefore, effectively relieving pain and repairing cartilage are crucial issues that urgently need to be addressed in the treatment of KOA.
[0003] Voltage-gated sodium ion channel 1.7 (Nav1.7) has become a promising analgesic target in recent years. Studies have shown that Nav1.7 is functionally expressed in chondrocytes of osteoarthritis patients, and its expression level is positively correlated with pain levels. Natural toxic peptides, with their target specificity and potent effects, are an important source of ion channel blockers. For example, the Ssm6a peptide isolated from the venom of *Scolopendra subspinipes* can effectively inhibit Nav1.7, exhibiting superior analgesic effects compared to morphine. WO2014165277A2 discloses selective Nav1.7 inhibitor peptide analogs (such as JzTx-V) that address the challenge of off-target effects in pain management by specifically targeting the Nav1.7 channel, enhancing pain relief while minimizing impacts on cardiac and skeletal muscle excitability. However, the free peptide SaTx is easily degraded by enzymes in vivo, has a short half-life, requires repeated intra-articular injections, and suffers from poor patient compliance, significantly limiting its clinical translation. Loading peptides into suitable delivery systems is a common approach to address these issues.
[0004] Hydrogels are widely used as drug delivery carriers due to their high water content, good biocompatibility, and tunable mechanical properties. In particular, injectable self-healing hydrogels, with their dynamic cross-linked networks, can rapidly gel and adhere to damaged tissue surfaces under physiological conditions. They not only act as a protective barrier for cartilage but also enable local controlled and sustained release of drugs, improving bioavailability. However, existing hydrogel systems generally use physical embedding or non-specific mixing to load peptides, making it difficult to avoid initial burst release and activity loss during storage and delivery. Furthermore, the formation of the gel network itself largely depends on external cross-linking agents or harsh conditions; the peptides merely exist as carriers and do not participate in the construction of the gel structure, resulting in the inability to fundamentally protect peptide activity and making precise control of sustained-release behavior difficult. Current reports indicate that Nav1.7 inhibitor peptides are mainly used for analgesia, but for the treatment of KOA, analgesia is only a symptomatic treatment. Effective loading of the peptide while simultaneously achieving analgesia, anti-inflammation, and cartilage repair would be a more effective treatment approach. Therefore, how to design a self-healing Nav1.7 inhibitory peptide gel that can achieve sustained release of peptides and synergistic effects of analgesia, anti-inflammation, and cartilage repair, thereby effectively treating KOA, is a problem that needs to be solved. Summary of the Invention
[0005] To address the aforementioned limitations of existing technologies, the present invention aims to provide a self-healing Nav1.7 inhibitory peptide gel, its preparation method, and its applications. This invention uses the Nav1.7 inhibitory peptide SaTx as the cross-linking core to prepare a dynamic self-healing gel. Utilizing the abundant active groups on the SaTx polypeptide chain, it serves as a molecular cross-linking hub, allowing chemically modified polyglutamic acid and chitosan to be covalently anchored to the same SaTx peptide chain, forming a unique star-shaped multi-network cross-linked structure with SaTx as the core. This design overturns the traditional loading mode of peptides in gels, achieving zero burst release and responsive degradation-based sustained release of SaTx. Furthermore, it integrates multiple functions such as long-acting analgesia, highly effective anti-inflammation, and promotion of cartilage repair, achieving a synergistic effect of "analgesia-anti-inflammation-cartilage repair" in KOA treatment, solving the problem of harsh conditions and insignificant efficacy associated with free peptides.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A first aspect of the present invention provides a method for preparing a self-healing Nav1.7 inhibitory peptide gel, comprising the following steps: (1) Polyglutamic acid was dissolved in 2-(N-morpholine) ethanesulfonic acid buffer, dopamine hydrochloride was added, and the reaction was carried out in the dark under the activation of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide. After dialysis and lyophilization, catechol-modified polyglutamic acid was obtained, which was denoted as PGA-Cat. (2) Dissolve chitosan in acetic acid solution, add 2-iminothione hydrochloride, adjust pH to 7.0-8.0, react under a protective atmosphere, and then obtain thiolated chitosan by dialysis and freeze drying, denoted as CS-SH; (3) Under ice bath conditions, PGA-Cat obtained in step (1) and CS-SH obtained in step (2) are dissolved in lactic acid solution. Tyr·HCl and EDC·HCl are added under ice bath conditions to obtain precursor mixed solution. Then Nav1.7 inhibitory peptide SaTx solution is added and quickly mixed. Then N-hydroxysuccinimide is added and stirred until completely dissolved. After standing at room temperature for crosslinking, self-healing Nav1.7 inhibitory peptide gel (SaTx-Gel) is obtained.
[0007] Preferably, in step (1), the mass ratio of polyglutamic acid to dopamine hydrochloride is 2:1; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 2:1.
[0008] Preferably, in step (1), the light-protected reaction time is 12h; the dialysis is performed using a dialysis bag with a molecular weight of 500D to obtain a retentate; and the freeze-drying temperature is -105℃ and the time is 24h.
[0009] Preferably, in step (2), the mass ratio of chitosan to 2-iminothion hydrochloride is 1:3.
[0010] Preferably, in step (2), the reaction temperature is room temperature and the time is 24h; the dialysis is performed using a dialysis bag with a molecular weight of 1000D to obtain a retentate; the freeze-drying temperature is -105℃ and the time is 24h.
[0011] Preferably, in step (3), the mass ratio of PGA-Cat and CS-SH is 1:1; the Nav1.7 inhibitory peptide SaTx solution is prepared from PBS solution with a concentration of 1.44 mg / mL; the amino acid sequence of the Nav1.7 inhibitory peptide SaTx is shown in SEQ ID NO:1, specifically: YCQKWMWTCDSKRKCCEGMVCKLWCKKIL.
[0012] Preferably, in step (3), the room temperature static crosslinking time is 5 min.
[0013] In a second aspect, the present invention provides a self-healing Nav1.7 inhibitory peptide gel obtained by the above preparation method, comprising a dual-network structure. The first network is formed by covalent bonds between the free amino groups of the Nav1.7 inhibitory peptide SaTx peptide chain and the catechol groups of polyglutamic acid modified with catechol groups. The second network is formed by dynamic disulfide bonds between the free thiol groups of the Nav1.7 inhibitory peptide SaTx peptide chain and the thiol groups of thiolated chitosan. The concentration of Nav1.7 inhibitory peptide SaTx in the self-healing Nav1.7 inhibitory peptide gel is 14.4 μg / mL.
[0014] A third aspect of the invention provides the use of self-healing Nav1.7 inhibitory peptide gel in the preparation of medicaments for the prevention, relief or treatment of knee osteoarthritis.
[0015] Preferably, the applications include increasing the mechanical pain threshold and / or thermal pain threshold; reducing synovial inflammation; reducing osteophyte formation; and protecting or repairing articular cartilage.
[0016] The beneficial effects of this invention are: (1) This invention establishes SaTx as the cross-linking core and necessary condition for gel network formation for the first time, and prepares a SaTx-structure-dependent two-component hydrogel (PGA-Cat / CS-SH / SaTx system). Control experiments clearly show that the PGA-Cat and CS-SH mixture alone is only a flowable viscous liquid, and gelation is rapidly triggered only after the addition of SaTx. This realizes the fundamental role transformation of SaTx from drug loading to carrier component.
[0017] (2) This invention establishes a novel drug sustained-release paradigm with a single core and a dual-network structure, achieving zero burst release and precise responsive release. SaTx, as the network backbone itself, transforms its release mechanism from physical diffusion to network degradation driven by chemical bond breaking, completely eliminating early burst release. Under the physiological environment of the joint cavity, the gradual breaking of disulfide and amide bonds ensures that the release rate of SaTx is completely synchronized with the gel degradation rate. By adjusting the amount of SaTx added to change the crosslinking density, the degradation cycle of the gel can be customized, achieving long-term sustained release over several days to several weeks, greatly extending the dosing interval.
[0018] (3) This invention fully leverages the dual core roles of SaTx in both structure and function to achieve synergistic effects. The dynamic disulfide bond network constructed by SaTx not only provides the gel with excellent injectable self-healing properties, but also gives the gel unique mechanical adaptability and seamless tissue adhesion. In the joint cavity, the gel can act as a protective barrier and lubricant for cartilage, and continuously release SaTx molecules during degradation, achieving sustained inhibition of Nav1.7 channels, effective regulation of the inflammatory microenvironment, and continuous promotion of chondrocyte proliferation. The structural protection and drug treatment are perfectly unified, and the comprehensive efficacy is significantly better than any single method.
[0019] (4) The preparation process of this invention is ingenious and the conditions are mild, resulting in extremely high peptide activity retention and industrial feasibility. The active groups of the peptide are directly used as chemical cross-linking sites for the gel, and the entire process is carried out in an aqueous phase, at room temperature, or in an ice bath, without the need for any organic solvents or harsh conditions, thus maximizing the protection of the biological activity and higher-order structure of SaTx. This design significantly simplifies the process, reduces the loss of expensive raw materials, keeps costs under control, and is suitable for large-scale production. Attached Figure Description
[0020] Figure 1 (a) Photograph of SaTx-Gel prepared in Example 1 after standing; (b) Photograph of SaTx-Gel prepared in Example 1 after being inverted for 5 min; (c) Photograph of PGA / CS-Gel prepared in Comparative Example 1 after standing; (d) Photograph of PGA / CS-Gel prepared in Comparative Example 1 after being inverted for 5 min; (e) Photograph of SaTx / CS-Gel prepared in Comparative Example 2 after standing; (f) Photograph of SaTx / CS-Gel prepared in Comparative Example 2 after being inverted for 5 min; (g) Photograph of SaTx / PGA-Gel prepared in Comparative Example 3 after standing; (h) Photograph of SaTx / PGA-Gel prepared in Comparative Example 3 after being inverted for 5 min. Figure 2 (a) Self-healing properties of SaTx-Gel; (b) Injectability testing; (c) Self-healing properties of PGA / CS-Gel; Figure 3 (a) Scanning electron microscope (SEM) image of SaTx-Gel; (b) Scanning electron microscope (SEM) image of SaTx / PGA-Gel; (c) Scanning electron microscope (SEM) image of SaTx / CS-Gel; (d) Scanning electron microscope (SEM) image of PGA / CS-Gel; Figure 4 (a) Adhesion of SaTx-Gel to polypropylene centrifuge tubes; (b) Adhesion of SaTx-Gel to Teflon plastic pipette tips; (c) Adhesion of SaTx-Gel to glass petri dishes; (d) Adhesion of SaTx-Gel to stainless steel spatulas; (e) 0° finger bending adhesion test; (f) 30° finger bending adhesion test; (g) 60° finger bending adhesion test; (h) 90° finger bending adhesion test. Figure 5 SaTx sustained-release curve; Figure 6(a) Expression level of pro-inflammatory cytokine IL-6 in cell supernatant after 12 h of SaTx-Gel treatment; (b) Expression level of pro-inflammatory cytokine IL-6 in cell supernatant after 24 h of SaTx-Gel treatment; (c) Expression level of pro-inflammatory cytokine TNF-α in cell supernatant after 12 h of SaTx-Gel treatment; (d) Expression level of pro-inflammatory cytokine TNF-α in cell supernatant after 24 h of SaTx-Gel treatment. Figure 7 (a) Changes in rat body weight; (b) Weight gain rate on day 14; (c) Thermal pain threshold; (d) Rate of change in thermal pain threshold on day 14; (e) 50% mechanical pain threshold; (f) Rate of change in mechanical pain threshold on day 14. The red arrows in the figure indicate the injection time of MIA, and the black arrows indicate the administration time of SaTx or other groups. Figure 8 (a) Effect of SaTx-Gel on IL-6 expression level; (b) Effect of SaTx-Gel on TNF-α expression level; Figure 9 (a) Morphological image of rat knee joint; (b) Three-dimensional reconstructed image of rat knee joint using Micro-CT scan; Figure 10 H&E staining results of rat knee joints; Figure 11 Masson staining results of rat knee joint; Figure 12 (a) Western blot images of PI3K, Akt, and IL-10 protein expression levels; (b) quantification of PI3K protein grayscale values; (c) quantification of Akt protein grayscale values; (d) quantification of IL-10 protein grayscale values; Figure 13 (a) RP-HPLC analysis of SaTx after refolding; (b) Schematic diagram of the disulfide bond linkage mode of SaTx. Detailed Implementation
[0021] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0022] As described in the background section, while free Nav1.7 inhibitory peptide SaTx has the potential for highly effective analgesia and cartilage repair, its short half-life and easy degradation in vivo limit its clinical application. Although existing hydrogel delivery systems can load drugs, most have only one function and cannot simultaneously meet the requirements of the complex mechanical environment within the joint cavity for self-repair, injectability, tissue adhesion, and long-lasting sustained release.
[0023] Based on this, the purpose of this invention is to provide a self-healing Nav1.7 inhibitory peptide gel, its preparation method, and its application. The self-healing Nav1.7 inhibitory peptide gel prepared by this invention has a dual-network structure: the first network is formed by covalent bonds between the free amino groups of the Nav1.7 inhibitory peptide SaTx peptide chain and the catechol groups of polyglutamic acid modified with catechol groups; the second network is formed by dynamic disulfide bonds between the free thiol groups of the Nav1.7 inhibitory peptide SaTx peptide chain and the thiol groups of thiolated chitosan, thereby loading SaTx within the network. PGA and CS, as natural polymers, provide good biocompatibility and degradability. The introduced Tyr·HCl, under the action of crosslinking agent EDC / NHS and oxygen in the air, generates phenolic oxygen radicals, which then undergo CC or COC coupling, forming dynamically reversible chemical crosslinking points. This physical / chemical dual-network structure endows the gel with a strong energy dissipation mechanism, enabling it to rapidly self-heal and restore its three-dimensional network structure after successful injection following shear thinning, and to firmly adhere to the surface of moist cartilage tissue. This gel not only serves as a drug reservoir, enabling the continuous and stable release of SaTx within the joint cavity, but its physical barrier function, along with the anti-inflammatory and antibacterial activities of the chitosan component and the activity of polyglutamic acid, can also synergize with the biological effects of SaTx to jointly inhibit inflammation and protect and repair cartilage.
[0024] To enable those skilled in the art to better understand the technical solution of this application, the technical solution of this application will be described in detail below with reference to specific embodiments.
[0025] The Nav1.7 inhibitory peptide SaTx was first isolated and purified from the venom of *Selenocosmia longiembola* (long-spined spider). The Nav1.7 inhibitory peptide SaTx used in this invention has a known amino acid sequence (YCQKWMWTCDSKRKCCEGMVCKLWCKKIL). Following the method described in *Caffeic Acid Modified Nanomicelles Inhibit Articular Cartilage Deterioration and Reduce Disease Severity in Experimental Inflammatory Arthritis* (Akshay Vyawahare, ACS Nano, Vol. 16, Issue 11, 18579–18591), a linear polypeptide was prepared using Fmoc amino acid solid-phase synthesis. Specifically: Fmoc-Arg-Wang resin was swollen with DMF to ensure sufficient swelling of the resin particles, facilitating the entry of subsequent reagents into the internal reaction sites. The initial amino protection state of the resin was confirmed by Kaiser Test. A deprotecting agent was added to remove the Fmoc protecting group at the N-terminus of the amino acid, and Kaiser Test was used to verify whether the amino group was exposed. Simultaneously, the next amino acid was premixed and activated with the coupling agent HBTU, and then added to the resin tube for reaction, with Kaiser Test used to verify whether the new amino acid was successfully linked. After each step, the peptide was thoroughly washed with DCM and DMF to remove excess reagents and byproducts. The target peptide was synthesized sequentially up to the last amino acid. A lysis buffer was used to react for an extended period under ice bath conditions to cleave the peptide from the Wang resin, while simultaneously removing the protecting groups of the amino acid side chains. After precipitating and washing with diethyl ether, the precipitate was collected by centrifugation and resuspended in ultrapure water. Impurities and resin residues were removed by filtration through a 0.22 μm membrane. The peptide powder was then removed by vacuum freeze-drying and stored in a sealed container at -20°C.
[0026] For the obtained linear peptide, referring to the method in Centipedes subdue giant prey by blocking KCNQ channels (Lei Luo, PNAS, 2018, Vol. 115, Issue 7, 1646–1651), refolding was performed using the GSH / GSSG redox buffer system, specifically as follows: The linearly reduced peptide was dissolved in 0.1 M Tris-HCl-0.1 M sodium chloride buffer (pH 8.0) containing 5 mM reduced glutathione and 0.5 mM oxidized glutathione, and the final concentration was adjusted to 30 μM. The reaction was carried out at 28°C for 24 hours to complete oxidative folding. The peptide was then separated by a linear gradient of acetonitrile using a C18 reversed-phase column, and the purity of the oxidized peptide was verified by MALDI-TOF-MS. After HPLC purification and lyophilization, refolded SaTx was obtained. Figure 13 (a) It can be seen that the purity is greater than 97%. Furthermore, comparison with protein / DNA sequence databases revealed that the SaTx disulfide bond linkage mode is as follows: Figure 13 (b) shows the standard ICK type pairings of type I–IV, II–V, and III–VI.
[0027] The test materials used in the embodiments of this invention are all conventional test materials in the art and can be purchased through commercial channels.
[0028] Example 1: Preparation of self-healing Nav1.7 inhibitory peptide gel (SaTx-Gel) (1) Dissolve 1.5 g of polyglutamic acid in 10 mL of 2-(N-morpholine) ethanesulfonic acid buffer, add 0.75 g of dopamine hydrochloride, and react in the dark for 12 h (overnight) under the activation of 0.48 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.29 g of N-hydroxysuccinimide. After dialyzing with a dialysis bag with a molecular weight of 500D, freeze-dry the retentate at -105℃ for 24 h to obtain catechol-modified polyglutamic acid, denoted as PGA-Cat.
[0029] (2) Dissolve 1g of chitosan in 10mL of 1% acetic acid solution (prepared by adding 1g of acetic acid to 100mL of water), add 3g of 2-iminothionine hydrochloride, adjust the pH to 7.0-8.0, react under N2 for 24h, dialyze using a dialysis bag with a molecular weight of 1000D, freeze-dry the retentate at -105℃ for 24h to obtain thiolated chitosan, denoted as CS-SH.
[0030] (3) Add 1.5 g PGA-Cat and 0.2 g CS-SH to 10 mL of 0.1% lactic acid solution (prepared by adding 0.1 g lactic acid to 100 mL of water) and stir to dissolve at room temperature. Under ice bath conditions, add 1.0 g Tyr·HCl (tyramine hydrochloride) and stir to dissolve. Then add 0.2 g EDC·HCl (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride) and stir under ice bath conditions for 2 minutes to activate the carboxyl groups of PGA and CS. Add 0.1 mL of SaTx solution (concentration of 1.44 mg / mL) that has been dissolved in PBS to the above mixture and stir until homogeneous. Finally, add 0.2 g NHS (N-hydroxysuccinimide) and stir rapidly until completely dissolved. Immediately pour into a mold and let stand at room temperature for 5 minutes to obtain the self-healing gel loaded with SaTx (SaTx-Gel, 10 mL). The theoretical final concentration of SaTx in the prepared SaTx-Gel is approximately 14.4 μg / mL. The gel is transparent and does not flow when inverted, confirming that it has formed a gel.
[0031] Comparative Example 1 The difference from step (1) of Example 1 is that SaTx solution is not added. PGA / CS-Gel is finally prepared.
[0032] Comparative Example 2 The difference from step (1) of Example 1 is that PGA-Cat is not added. SaTx / CS-Gel is finally prepared.
[0033] Comparative Example 3 The difference from step (1) of Example 1 is that CS-SH is not added. SaTx / PGA-Gel is finally prepared.
[0034] Comparative Example 4 The difference from step (3) of Example 1 is as follows: 1.5 g PGA-Cat and 0.2 g CS-SH were added to 10 mL of 0.1% lactic acid solution (prepared by adding 0.1 g lactic acid to 100 mL of water) and stirred at room temperature to dissolve. Under ice bath conditions, 1.0 g Tyr·HCl (tyramine hydrochloride) was added and stirred to dissolve. Then, 0.2 g EDC·HCl (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride) was added and stirred under ice bath conditions for 2 minutes to activate the carboxyl groups of PGA and CS. 0.2 g NHS (N-hydroxysuccinimide) was added and stirred rapidly for 3 minutes. Then, 0.1 mL of SaTx solution (concentration of 1.44 mg / mL) that had been dissolved in PBS was added and stirred evenly. The solution was immediately poured into a mold and allowed to stand at room temperature for 5 minutes. The resulting hydrogel (10 mL) was denoted as PGA / CS-Gel-SaTx.
[0035] Example 2: Characterization The materials should be added according to the requirements of the above embodiments and comparative examples. Figure 1 (e)~ Figure 1 As shown in (h), Comparative Examples 2 and 3 synthesized were in a semi-fluid state, exhibiting only weak gel-forming ability and good self-healing properties, but their mechanical strength was significantly insufficient; as Figure 1 (c) and Figure 1 As shown in (d), Comparative Example 1 is a solid. The lack of SaTx introduction results in good mechanical strength, but it is brittle under compression and stretching. The gels mentioned above all have poor performance due to their overly simple molecular network. Figure 1 (a) and Figure 1 (b) A dual-network structure was introduced to obtain the gel of Example 1, which can quickly and efficiently self-heal and has good mechanical properties.
[0036] To investigate the microstructure, pore size distribution, and network structure characteristics of each gel group, scanning electron microscopy (SEM) was used to observe the internal microstructure of the SaTx-Gel prepared in Example 1 and the gels prepared in Comparative Examples 1-3. Figure 3As shown, after freeze-drying, the gel samples of each group were subjected to liquid nitrogen fracture treatment, gold sputtering treatment, and then their pore structure was observed under a scanning electron microscope. SaTx / CS-Gel and SaTx / PGA-Gel showed a loose and partially collapsed macroporous structure with smooth pore walls and poor three-dimensional network integrity, confirming that neither had good mechanical strength. PGA / CS-Gel showed a regular, typical thick sheet-like stacked structure, confirming its poor fluidity and self-healing properties. SaTx-Gel exhibited the most ideal microstructure, with a uniformly distributed honeycomb interconnected network visible under the microscope. The pores were relatively uniformly distributed with smooth and continuous pore walls, without obvious collapse or breakage and with high regularity, indicating that compared with the PGA / CS-Gel group, SaTx can promote the formation of a stable double network structure after participating in gel cross-linking.
[0037] Further testing was conducted on the self-healing properties of SaTx-Gel and PGA / CS-Gel gels, both exhibiting good mechanical strength. The gel samples were cut into two parts, ensuring full contact at the fracture interface, and allowed to stand at room temperature for 30 minutes to observe the gel reconnection. The results are as follows: Figure 2 (a) and Figure 2 As shown in (c), SaTx-Gel can heal itself without external stimulation. The healed sample can withstand a certain degree of stretching without breaking, while PGA / CS-Gel only undergoes simple physical adhesion and breaks at the original incision after being stretched to a certain degree. This indicates that the dynamic cross-linking network constructed by SaTx gives the gel good self-healing ability.
[0038] To evaluate the suitability of the selected SaTx-Gel, we assessed its injectability and adhesion using syringe extrusion and gel adhesion experiments. Figure 2 As shown in (b), SaTx-Gel can pass smoothly through the injection needle and maintain its intact gel shape after extrusion, indicating that the gel has good shear response and injectability, and is suitable for local intra-articular drug delivery. Figure 4 The results showed that the hydrogel exhibited certain adhesion to materials such as plastics, glass, and stainless steel. In the finger bending adhesion test, the hydrogel was able to adhere closely to the finger skin and deform with the bending and stretching of the finger without falling off, demonstrating excellent flexibility and dynamic tissue compliance.
[0039] Example 3: In vitro sustained-release properties of self-healing gel loaded with SaTx Simultaneously, the release behavior of SaTx in different gel systems was compared. SaTx-Gel, SaTx / PGA-Gel, SaTx / CS-Gel, and PGA / CS-Gel-SaTx were weighed and immersed in centrifuge tubes containing 10 mL of PBS (pH 7.4), and placed in a 37℃ constant temperature shaking incubator (100 rpm). At preset time points (1h, 2h, 4h, 8h, 12h, 1d, 2d, 3d, 4d), 2 mL samples were taken, and an equal volume of fresh PBS was added. The concentration of SaTx in the sample solution was determined by HPLC, and a cumulative release curve was plotted. HPLC detection conditions: C18 reversed-phase column, mobile phase: water / acetonitrile system containing 0.1% trifluoroacetic acid, gradient elution, detection wavelength: 214 nm. Results are as follows: Figure 5 As shown.
[0040] according to Figure 5 It can be seen that all gel groups achieved sustained release of SaTx. Among them, SaTx-Gel had a flatter release curve, without a significant rapid release in the initial stage, but maintained a sustained release trend within 4 days, with a final cumulative release rate of approximately 80%. Compared with other groups, SaTx-Gel exhibited more stable sustained-release characteristics. These results indicate that, because SaTx participates in the gel network construction, its release process is not only affected by diffusion but also regulated by gel network degradation and dynamic bond breaking, thus effectively reducing the initial burst release of the drug and achieving long-acting delivery.
[0041] Example 4: In vitro anti-inflammatory activity of self-healing gel loaded with SaTx Induction was achieved by adding IL-1β (10 ng / mL) to mouse chondrocyte progenitor cells ATDC5 (BTCC cell bank), with a density of 5 × 10⁶ cells / mL. 4 -1×10 5Two mL of cell suspension (cells / mL) was seeded into 6-well plates and incubated for 24 h. The cells were then replaced with serum-free medium and starved for 12 h, followed by induction medium and cultured for another 24 h to establish an in vitro osteoarthritis inflammation model. After model establishment, the medium was replaced with serum-free medium. Extracts were extracted from each gel group at a rate of 0.4 g gel / mL (the extract was collected after 12 h of serum-free medium extraction). Experimental groups were: blank control group (Control, PBS), inflammation model group (IL-1β), positive control group (Dexamethasone, 14.4 μg / mL), free SaTx group (SaTx, 14.4 μg / mL), comparative example 1 group (PGA / CS-Gel extract), and example 1 group (SaTx-Gel extract). Each group had a culture volume of 2 mL. Cell culture supernatants were collected after 12 and 24 hours of drug treatment, and the expression levels of inflammatory factors IL-6 and TNF-α were detected using an ELISA kit (Lianke Biotechnology).
[0042] ELISA test results as follows Figure 6 As shown in the figure, compared with the control group, the levels of IL-6 and TNF-α in the cell culture medium were significantly increased after IL-1β stimulation, indicating that the inflammation model was successfully established.
[0043] Compared with the IL-1β group, all treatment groups reduced the release of inflammatory factors to varying degrees. Specifically, the SaTx-Gel treatment group showed significantly reduced levels of IL-6 and TNF-α expression at 12 h and 24 h, with a greater degree of reduction than the free SaTx group and the PGA / CS-Gel group. These results indicate that SaTx-Gel can effectively inhibit the release of pro-inflammatory factors induced by inflammatory stimulation and enhance the sustained anti-inflammatory effect of SaTx through gel-based sustained release.
[0044] Example 5: Therapeutic effect of SaTx-loaded self-healing gel on knee osteoarthritis in rats A knee osteoarthritis (KOA) model was established in SD rats (Jinan Pengyue) by intra-articular injection of 20 μL of 50 mg / mL sodium iodoacetate (MIA) solution. A 50 mg / mL MIA solution was prepared in advance. MIA powder was weighed into centrifuge tubes according to the required dosage, dissolved in 0.9% physiological saline, and the centrifuge tubes were wrapped in aluminum foil to protect the MIA solution from light. The rats were anesthetized by intraperitoneal injection of 3% sodium pentobarbital, based on their body weight. After the rats became comatose, they were laid flat on the operating table, and double-sided ear tags with numbers were attached to their ears and recorded. All hair near the right hind knee joint was shaved off. After disinfection with alcohol, 20 μL of physiological saline was injected into the knee joint cavity using an insulin injection needle in the normal control group, while 20 μL of the prepared 50 mg / mL MIA solution was injected into the other groups using an insulin injection needle. After injection, the rat's knee joint was flexed back and forth five times to allow the solution to fully exert its effect within the joint cavity. After one day of normal feeding, the rat's right hind leg was pressed to determine the success of the modeling. Three days after modeling, the successfully modeled rats were randomly divided into four groups: a normal control group (Control), a model group (KOA, PBS), a control group (PGA / CS-Gel), a positive control group (Dexamethasone, 14.4 μg / mL), a free SaTx group (SaTx, 14.4 μg / mL), and a SaTx-loaded gel group (SaTx-Gel), with six rats in each group. The drug-treated groups received intra-articular injections of the above concentrations (30 μL each time) on days 4, 7, and 10 after modeling. The gel group received 30 μL of gel. The 50% mechanical pain threshold and thermal pain threshold were measured in all rats the day after each administration and at the experimental endpoint. Rats were sacrificed on day 13, and serum was collected to detect IL-6 and TNF-α levels. Knee joints were harvested for morphological observation, Micro-CT reconstruction, and histopathological staining with H&E and Masson's staining. Body weight changes in each group were recorded during the experiment. Results are as follows: Figures 7-11 As shown.
[0045] The results are as follows Figure 7 (a) ~ Figure 7 As shown in (b), the body weight of rats in each treatment group showed a gradual increasing trend, and there was no significant difference between the treatment groups, indicating that SaTx-Gel treatment did not cause significant systemic toxicity.
[0046] The 50% mechanical pain threshold was determined using the von Frey mechanical stimulation method, and the thermal pain threshold was determined using the hot plate stimulation method. The results are as follows: Figure 7 (c)~ Figure 7As shown in (f), the mechanical pain threshold and thermal pain threshold of rats in the KOA model group were significantly reduced after MIA induction. After treatment, the mechanical pain threshold and thermal pain threshold of rats in the SaTx-Gel group were significantly restored, and the restoration effect was better than that of the free SaTx group and the PGA / CS-Gel group, indicating that SaTx-Gel can effectively relieve KOA-related pain.
[0047] Further testing was conducted to determine serum inflammatory factor levels. Results were as follows: Figure 8 As shown, serum IL-6 and TNF-α levels were significantly elevated in the KOA model group, while the levels of both inflammatory factors decreased significantly after SaTx-Gel treatment, indicating that SaTx-Gel can improve the inflammatory microenvironment of KOA.
[0048] Subsequently, the knee joints of each group were visually observed and subjected to Micro-CT scans. The results are as follows: Figure 9 As shown, the KOA group showed obvious joint surface damage and bone structure abnormalities, while the SaTx-Gel group had a more intact joint surface, reduced bone structure damage, and decreased osteophyte formation.
[0049] H&E staining and Masson staining were used to observe changes in joint tissue structure. Results are as follows: Figure 10 and Figure 11 As shown, the KOA group exhibited significant cartilage structure destruction, inflammatory cell infiltration, and collagen fiber disorder; after SaTx-Gel treatment, the cartilage tissue structure was significantly restored, inflammatory infiltration was reduced, and collagen arrangement was more regular, demonstrating a better cartilage protection and repair effect.
[0050] Example 6: Study on the mechanism of action of self-healing gel loaded with SaTx The expression of PI3K / Akt signaling pathway-related proteins in the knee cartilage tissue of rats in Example 5 was detected by Western blotting. The Western blotting results are as follows: Figure 12 As shown.
[0051] according to Figure 12As can be seen, compared with the Control group, IL-1β stimulation significantly increased the expression levels of PI3K and Akt proteins, while decreasing the expression level of IL-10 protein, indicating that inflammatory stimulation activates the PI3K / Akt-related inflammatory signaling pathway. Compared with the IL-1β group, the Dex group, SaTx group, and SaTx-Gel group all reduced the expression of PI3K and Akt proteins and promoted the expression of IL-10 protein. Among them, the SaTx-Gel group showed the most significant regulatory effect on the PI3K / Akt signaling pathway, with the largest decrease in PI3K and Akt expression, while the IL-10 expression level was significantly increased. These results indicate that SaTx-Gel can not only exert a Nav1.7 inhibitory effect through sustained release of SaTx, but also regulate the PI3K / Akt signaling pathway and promote the expression of anti-inflammatory factors, thereby achieving analgesic, anti-inflammatory, and chondrogenic effects.
[0052] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing a self-healing Nav1.7 inhibitory peptide gel, characterized in that, Includes the following steps: (1) Polyglutamic acid was dissolved in 2-(N-morpholine) ethanesulfonic acid buffer, dopamine hydrochloride was added, and the reaction was carried out in the dark under the activation of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide. After dialysis and lyophilization, catechol-modified polyglutamic acid was obtained, which was denoted as PGA-Cat. (2) Dissolve chitosan in acetic acid solution, add 2-iminothione hydrochloride, adjust pH to 7.0-8.0, react under a protective atmosphere, and then obtain thiolated chitosan by dialysis and freeze drying, denoted as CS-SH; (3) Under ice bath conditions, PGA-Cat obtained in step (1) and CS-SH obtained in step (2) are dissolved in lactic acid solution. Tyr·HCl and EDC·HCl are added under ice bath conditions to obtain precursor mixed solution. Then Nav1.7 inhibitory peptide SaTx solution is added and quickly mixed. Then N-hydroxysuccinimide is added and stirred until completely dissolved. After standing at room temperature for crosslinking, self-healing Nav1.7 inhibitory peptide gel is obtained.
2. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of polyglutamic acid to dopamine hydrochloride is 2:1; the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is 2:
1.
3. The preparation method according to claim 1, characterized in that, In step (1), the light-protected reaction time is 12h; the dialysis is performed using a dialysis bag with a molecular weight of 500D to obtain the retentate; the freeze-drying temperature is -105℃ and the time is 24h.
4. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of chitosan to 2-iminothion hydrochloride is 1:
3.
5. The preparation method according to claim 1, characterized in that, In step (2), the reaction temperature is room temperature and the time is 24h; the dialysis is performed using a dialysis bag with a molecular weight of 1000D to obtain the retentate; the freeze-drying temperature is -105℃ and the time is 24h.
6. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of PGA-Cat and CS-SH is 1:1; the Nav1.7 inhibitory peptide SaTx solution is prepared with PBS solution and has a concentration of 1.44 mg / mL; the amino acid sequence of the Nav1.7 inhibitory peptide SaTx is shown in SEQ ID NO:1, specifically: YCQKWMWTCDSKRKCCEGMVCKLWCKKIL.
7. The preparation method according to claim 1, characterized in that, In step (3), the room temperature static crosslinking time is 5 min.
8. The self-healing Nav1.7 inhibitory peptide gel obtained by the preparation method according to any one of claims 1 to 7, characterized in that, The gel comprises a dual-network structure. The first network is formed by covalent bonds between the free amino groups of the Nav1.7 inhibitory peptide SaTx and the catechol groups of polyglutamic acid modified with catechol groups. The second network is formed by dynamic disulfide bonds between the free thiol groups of the Nav1.7 inhibitory peptide SaTx and the thiol groups of thiolated chitosan. The concentration of Nav1.7 inhibitory peptide SaTx in the self-healing Nav1.7 inhibitory peptide gel is 14.4 μg / mL.
9. The use of the self-healing Nav1.7 inhibitory peptide gel according to claim 8 in the preparation of a medicament for the prevention, relief or treatment of knee osteoarthritis.
Citation Information
Patent Citations
POTENT AND SELECTIVE INHIBITORS OF Nav1.7
WO2014165277A2
